A Free, Open-Source Tool for Identifying Urban Agglomerations using Point Data. Issue 1 (2nd January 2016) - Day, Jennifer; Chen, Yiqun; Ellis, Peter; Roberts, Mark
Abstract: This paper describes a software tool for identifying urban agglomerations in low-information settings. The framework outlined in this paper is designed to work using point data. Our tool and all required data are provided free and in open-source format. This paper describes the advantages and disadvantages of using point-based geographies in regional analysis, discusses the practical and ethical challenges of distinguishing urban from rural regions, details the function of our software, and directs the interested reader to the source code. The paper also examines the tool's outputs for Sri Lanka and compares them with published United Nations urbanization figures. Our outputs indicate that Sri Lanka's urban population is significantly undercounted in official statistics.